Eight hundred grapes : a novel - Dave, Laura (Simon & Schuster, 2015)
"Bestselling author Laura Dave has been dubbed "a wry observer of modern love" ("USA TODAY"), a "decadent storyteller" ("Marie Claire"), and "compulsively readable" ("Woman's Day"). Set in the lush backdrop of Sonoma's wine country, "Eight Hundred Grapes" is a heartbreaking, funny, and deeply evocative novel about love, marriage, family, wine, and the treacherous terrain in which they all intersect."--